Prokrastinasi Akademik Mahasiswa Bimbingan dan Konseling Universitas Negeri Malang - Dimas Ivan Aminta; Djoko Budi Santoso; Elia Flurentin; Dimas Ivan Aminta; Djoko Budi Santoso (Universitas Negeri Malang, 2023)
Abstract: Changes in learning methods during the pandemic transition period are starting to return to normal. Activities outside of lectures such as student activity units began to be active again. Students are required to adapt and actively carry out activities on and off campus. Various cases faced by students cannot be avoided. Assignments in the form of individuals and groups with certain deadlines for collection. In the settlement of obligations as a student there are problems such as delays in work or assignments due to various factors. The behavior of procrastinating work in this case is also called academic procrastination behavior. This research is a quantitative study with a survey research design. The sample of this study was students majoring in Guidance and Counseling, State University of Malang batch 2020. The sampling technique used was simple random sampling. The research instrument is an inventory of academic procrastination. The data analysis technique is percentage. The results of the analysis showed that students belonging to the category of academic procrastination were 16 percent high. Students who belong to the category of moderate academic procrastination are 79 percent. students who belong to the category of low academic procrastination are 16 percent. students who belong to the category of academic procrastination are very low at 0 percent. It was concluded that the academic procrastination of Guidance and Counseling Department students was in the moderate category. This research can be used as data from the Department of Guidance and Counseling, State University of Malang and forwarded to LP2BK3A if the level of academic procrastination of Guidance and Counseling students at State University of Malang shows a high percentage and needs to be followed up. Abstrak: Perubahan Metode pembelajaran di masa transisi pandemi mulai kembali normal. Kegiatan-kegiatan diluar perkuliahan seperti unit kegiatan mahasiswa mulai aktif kembali. Mahasiswa dituntut beradaptasi dan aktif menjalani kegiatan di dalam dan diluar kampus. Berbagai kasus yang dihadapi para mahasiswa tidak dapat terhindar. Tugas dalam bentuk individu dan kelompok dengan tenggat waktu pengumpulan tertentu. Dalam penyelesaian kewajiban sebagai mahasiswa terdapat masalah seperti penundaan pekerjaan atau tugas karena berbagai macam faktor. Perilaku menunda-nunda pekerjaan dalam hal ini disebut juga dengan perilaku prokrastinasi akademik.Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian survei. Sampel penelitian ini adalah mahasiswa jurusan Bimbingan dan Konseling Universitas Negeri Malang angkatan 2020. Teknik penarikan sampel yang digunakan adalah simple random sampling. Instrumen penelitian ini adalah inventori prokrastinasi akademik. Teknik analisis datanya adalah persentase. Hasil analisis menunjukan mahasiswa yang termasuk kategori prokrastinasi akademiknya tinggi sejumlah 16 persen. Mahasiswa yang termasuk kategori prokrastinasi akademiknya sedang sejumlah 79 persen. mahasiswa yang termasuk kategori prokrastinasi akademiknya rendah sejumlah 16 persen. mahasiswa yang termasuk kategori prokrastinasi akademiknya sangat rendah sejumlah 0 persen. Disimpulkan bahwa prokrastinasi akademik mahasiswa Departemen Bimbingan dan Konseling dalam kategori sedang. Penelitian ini dapat dijadikan data Departemen Bimbingan dan Konseling Universitas Negeri Malang dan diteruskan kepada LP2BK3A apabila tingkat prokrastinasi akademik mahasiswa Bimbingan dan Konseling Universitas Negeri Malang menunjukan presentase yang tinggi dan perlu untuk di tindaklanjuti.